(3egGe GdabgGAs - (3eMeO cGej Hf EHQGgje Hf CMeO Hf SfGf GdnCpOrQnfphj,J (B1136 (3g` s
(3ChdgG (B:s
(3MeOkG def QaY dYfGjJg WHbGJ GdabgGA s
(3QJHg Ydi MQha GdeYLe hLYd ai BNQ cd MQa aUdkG ai CSeGA GdcJH GdabgjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B14 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B161s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B438 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B269 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCRgQ (B((3JGQjN CHGXI (B6550(242)) s
Keywords: (3GdJGQjNs